2008
DOI: 10.1007/s10620-008-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Carbohydrate Antigen 19.9 in Benign Hepatobiliary Conditions and Its Correlation with Serum Bilirubin Concentration

Abstract: CA19.9 level is significantly influenced by serum bilirubin and elevated levels have been observed in patients with non-malignant HPB conditions. Adjusting CA19.9 according to bilirubin levels is likely to improve the specificity of this antigen in the differential diagnosis of benign and malignant HPB diseases and its reliability in the monitoring of disease response to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 20 publications
1
56
1
1
Order By: Relevance
“…Ong et al studied 83 patients presenting with abnormal CA19-9 serum levels and radiological or clinical features suggestive of hepato-biliary-pancreatic (HPB) malignancy who were subsequently found to have benign disease. On multivariate analysis, these authors reported that hyperbilirubinemia (serum bilirubin >2 mg/dl) was an independent factor predictive of CA 19-9 serum level (p<0.028) [76,77]. Biliary drainage which results in a decrease in CA 19-9 serum levels suggests benign conditions.…”
Section: Limitations Of Ca 19-9 Serum Levels As a Pancreatic Cancer Bmentioning
confidence: 98%
“…Ong et al studied 83 patients presenting with abnormal CA19-9 serum levels and radiological or clinical features suggestive of hepato-biliary-pancreatic (HPB) malignancy who were subsequently found to have benign disease. On multivariate analysis, these authors reported that hyperbilirubinemia (serum bilirubin >2 mg/dl) was an independent factor predictive of CA 19-9 serum level (p<0.028) [76,77]. Biliary drainage which results in a decrease in CA 19-9 serum levels suggests benign conditions.…”
Section: Limitations Of Ca 19-9 Serum Levels As a Pancreatic Cancer Bmentioning
confidence: 98%
“…The mean ALP was 507.8 U/L before and 184.0 U/L after drainage in this group. Ong SL et al 15 found mean serum bilirubin 15.5mg/dl, range 1.2-26.0 mg/dl before biliary drainage and 8.2 mg/dl and range 1.2-14.5 mg/dl after biliary drainage in benign obstructive jaundice. The mean ALP in their study was 640 U/L before and 330 U/L after drainage.…”
Section: Discussionmentioning
confidence: 96%
“…CA 19-9 elevation in benign biliary tract disease has frequently been reported, but a very high level of CA 19-9 (>500 IU/ml) in such cases has rarely been observed (3)(4)(5)(6)(7)9). Mirizzi's syndrome and acute cholangitis are the usual definitive diagnoses of patients with these extreme values (4,7).…”
Section: Discussionmentioning
confidence: 98%